A joint unemployment insurance for the European Economic and Monetary Union? - Werner Eichhorst; Florian Wozny (Institute for the Study of Labor (IZA), 2014)
More and more policy makers tend to declare that the loss of exchange rate adjustments within the European Economic and Monetary Union (EMU) has to be compensated by an increase in fiscal policy. A joint unemployment insurance is seen as one opportunity. After comparing a basic design with a "kicking-in" style unemployment insurance, we recommend the latter as it captures the main motivation of such a transnational transfer mechanism, combating credit market constraints.
Keywords: J65; J68; 330; European Economic and Monetary Union; European unemployment insurance; automatic stabilizers